Conexões entre as habilidades da consciência fonológica e a produção escrita da criança: o trabalho de analise da sílaba na fase inicial de alfabetização - Macilene Vilma Gonçalves (2014)
This study falls within the field of research about the connections between a phonological consciousness and an alphabetic writing system appropriation. We investigated the implications of various phonological abilities in the writing of first grade school children. Phonological consciousness tests were taken at the beginning and at the end of the study. There were also production tasks with written word lists at three moments of the school year, and children were asked to justify their answers. A dialogue was established with studies from various viewpoints on phonological consciousness and with investigations about how learners relate speech and writing, and also about syllabic structure. Instability points in the subjects writing were discussed, based on four categories: problems with relevance disorder, influence of letters names recognition, the imposition of the CV model; influence of acquired knowledge about the spelling system in formal education. Our results provide evidence that, among phonological awareness, oral segmentation into syllables must be well established for the child to go through their process of writing evolution; that children operate with syllables, rhymes, alliterations and phonemes, however, even with alphabetic hypothesis, are not able to pronounce the phonemes and refer to the letters by their names. The phonological consciousness seems to have an evolution and variation and cannot be considered as if the child has it or not. In the study, supported by the their writing, the children operated with linguistic unities they cant operate in oral tasks. This indicates that the writing would be the starting point to speech analysis. Children have particular ways of analyzing the syllables in order to write and the solutions they find for problems with writing seems to depend on their concept hypothesis about the alphabetical writing system deriving from various types of phonological analyses they are capable of performing, and from the syllable internal frame. Besides phonological reflections, a child lives with other hypothesis they elaborate on syllables internal structure, its hardship hierarchy and an apparent need for the child to preserve the CV model, next to the decisions about which letters (consonants or vowels) and their writing order. Thus, our hypothesis is that childrens omissions when writing, cant be assigned (only) to phonemic analyses incapability.